American Catholic lay groups and transatlantic social reform in the progressive era - Moloney, Deirdre M. (University of North Carolina Press, 2002)
This text traces the development of social reform movements among American Catholics from 1880 to 1925. Deirdre M. Moloney reveals how Catholic gender ideologies, emerging middle-class values, and ethnic identities shaped the goals and activities of lay activists in this time.